Pengaruh gaya belajar dan belajar matematika realistis terhadap hasil belajar Siswa kelas V SDN 11 Lubuk Buaya Padang - Hasanah, Laila (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research was conducted because researchers wanted to know the influence of learning styles and the Realistic Mathematics Education (RME) learning model on student learning outcomes in fifth grade elementary school mathematics subjects. This research method is quantitative and is a type of Non Equivalent Pre-Test and Post-Test Control Group Design. The research sample for the experimental class was all class V students at SD Negeri 11 Lubuk Buaya, totaling 27 students and the control class was all class V students at SD Negeri 11 Lubuk Buaya, totaling 27 students. The data collection technique is in the form of 20 multiple choice test questions. The Independent Sample T-Test serves to test the hypothesis obtained by Sig. (2-tailed) of 0.000 < 0.05. Based on the results, it shows that Ha is accepted and Ho is rejected. It can be concluded that the application of the Realistic Mathematics Education learning style and learning model has an influence and the learning outcomes of class V students at SD Negeri 11 Lubuk Buaya Padang increase. It is known that the experimental class obtained an average pretest result of 65.25 and the control class pretest average was 65. Meanwhile, the posttest average of the experimental class was higher than the control class, namely 84 > 72.5.